Investigation of wind load alteration on rectangular cross-section tall building due to change in relative orientation of interfering building. (June 2021) - Chauhan, Bharat Singh; Chakrabarti, Anupam; Ahuja, Ashok Kumar
Abstract: The alteration of wind pressure distribution caused by the change in relative orientation of a closely located interfering building is studied here on a rectangular cross-sectional shape principal tall building. Interfering building having same cross-sectional shape and height as that of principal building is placed close and in-front of the principal building, with across-wind lengths of two buildings being in-line with each other, keeping one vertical edge of the interfering building in same position the internal angle between principal and interfering building is changed. Two independent type of measurements are undertaken for varying internal angle: (1) . Force Measurement (2) . Pressure Measurement. For purpose of validation, the results obtained from two independent measurements mentioned are compared later. The results obtained from force measurements are expressed in the form of two-dimensional X-Y plots, while that for pressure measurement are depicted in the form of mean and RMS wind pressure coefficient ( C P and C P ′ ) contour plots on all vertical faces of the principal building. It is noted from force measurement, that for internal angle of 0 0 principal building is fully shielded by the interfering building, in fact a negative drag is observed on the principal building. As the internal angle increases from 0 0 to 90 0 the shielding effect caused by the interfering building reduces, as the internal angle further increases from 90 0 to 180 0 a small but uniform increase in along wind force is noted. High magnitudes of across-wind forces and twisting moments are also noted in some cases. Contour plots of mean pressure coefficients give a detailed reason for results obtained with force measurement and also distinctly show the distribution of pressure across vertical faces of the principal building.